Artificial intelligence as a new artist - Кеdа, І. О. (ТДАТУ, 2021)
It is extremely unusual to see an AI then become human-like in its form of thinking and computational abilities. Surprisingly, it seems to us that we should expect that in the future such a mind will write a masterpiece symphony, which will be compared to Mozart and Beethoven. We just have to wait and watch this area of technology with delight.
Keywords: artificial intelligence; algorithm